The ETUI's list of hazardous medicinal products (HMPs) including cytotoxics and based on the EU CLP classification system of carcinogenic, mutagenic and reprotoxic (CMR) substances - Ian Lindsley; Tony Musu (European Trade Union Institute (ETUI), 2022)
Workers exposed to hazardous medicinal products (HMPs), or hazardous drugs, which are carcinogenic, mutagenic or reprotoxic substances (CMRs), within the meaning of the recently adopted Carcinogens, Mutagens and Reprotoxic Substances Directive (CMRD - Directive (EU) 2022/431), must be given specific training by their employers to prevent risks of adverse effects on their health. In order to help employers meet their obligations, the European Commission has to publish European guidelines for the safe management of HMPs at work, including cytotoxics, by the end of 2022, and must draw up a definition and establish an indicative list of HMPs that are CMRs, no later than 5 April 2025. The objective of this ETUI report and the list included is to identify which HMPs fall under the legislative scope of the CMRD in Europe, so that users of the European 2022 guidelines know which specific HMPs the guidelines now apply to, well ahead of the Commission's indicative list, to be published by 2025.
Keywords: 330